UDAN – Playing to Learn the Nuances of Entrepreneurship. (December 2016) - Shankar, Raj K.
Background. Entrepreneurship courses are ubiquitous across educational institutions. While pedagogical innovations are being experimented with, using games to teach the nuances of starting up are rare. Problem. A practice-oriented subject like entrepreneurship is difficult to be taught using traditional methods. The elusive nature of the subject (entrepreneurship), its actors (entrepreneurs) and their actions (entrepreneurial) only make it worse. Approach. UDAN (means 'Flight' in Hindi) is a game, which solves this challenge. It simulates every aspect of the startup process in an entrepreneur's journey. While running the game brings energy and enthusiasm amongst participants, it exposes them to the harsh realities, challenges and thrills of creating and running a startup. The Game. Participants are grouped into teams representing startups in an airplane manufacturing industry. Every team selects various key people for roles like CEO, HR, Sales, Finance, workforce etc. There are both government buyers as well as private airlines of different sizes making purchases. Buying raw materials, managing teams and their outputs, marketing, selling airplanes, negotiating prices, signing contracts, raising invoices, collecting payments, meeting quality standards and customer expectations are some experiences the game offers. Selecting a name, registering company with the local authorities, ensuring regulatory compliance, and filing returns are the other organizational activities that get simulated. Number of market and regulatory surprises are thrown in to expose participants to the realities of the business world. A debrief summarizes the lessons that the game offers. Practical Implications. Being an entrepreneur requires one to come to terms with numerous aspects of starting and running an enterprise. It does not entail doing only what you love doing. Entrepreneurship is a socially involved practice. The game gives participants a peek into the varied nuances of running a startup. It highlights the need for exposing themselves to number of aspects of starting and managing an enterprise. It prepares the ground for the faculty to deliver a course on entrepreneurship. Participants will be able to appreciate the variety of tools and techniques that a good entrepreneurship course offers.